2017
DOI: 10.1371/journal.pone.0175649
|View full text |Cite
|
Sign up to set email alerts
|

Significant association of RNF213 p.R4810K, a moyamoya susceptibility variant, with coronary artery disease

Abstract: BackgroundThe genetic architecture of coronary artery disease has not been fully elucidated, especially in Asian countries. Moyamoya disease is a progressive cerebrovascular disease that is reported to be complicated by coronary artery disease. Because most Japanese patients with moyamoya disease carry the p.R4810K variant of the ring finger 213 gene (RNF213), this may also be a risk factor for coronary artery disease; however, this possibility has never been tested.Methods and resultsWe genotyped the RNF213 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 58 publications
(73 reference statements)
4
39
0
Order By: Relevance
“…The exact pathogenesis is unknown, though genetic factors and disruption in angiogenesis or vasculogenesis have been implicated as potential etiologies . Importantly, some studies have even demonstrated a significant association between Moyamoya disease/syndrome and CAD, which is of particular relevance to this case …”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…The exact pathogenesis is unknown, though genetic factors and disruption in angiogenesis or vasculogenesis have been implicated as potential etiologies . Importantly, some studies have even demonstrated a significant association between Moyamoya disease/syndrome and CAD, which is of particular relevance to this case …”
Section: Discussionmentioning
confidence: 73%
“…6,7 Importantly, some studies have even demonstrated a significant association between Moyamoya disease/syndrome and CAD, which is of particular relevance to this case. 8,9 The association between Moyamoya disease/syndrome, CAD, and the TKI medication class may be reflected in the pathological lesions observed in these conditions. Imaging techniques, such as intravascular ultrasound virtual histology and coronary CTA, have shown culprit lesions demonstrating eccentric intimal thickening mainly composed of fibrous tissue, with a relatively small proportion of fatty tissue or necrotic core.…”
Section: Case Seriesmentioning
confidence: 99%
“…The presence of RNF213 4810G > A variant was at increased risk for ischemic stroke, which was largely attributable to large-artery atherosclerosis [36]. Recent reports have also described associations between RNF213 variants and extracranial systemic vasculopathy involving coronary, renal, and pulmonary arteries [37][38][39].…”
Section: Discussionmentioning
confidence: 97%
“…[31] RNF213 has been identi ed as a susceptibility gene of Moyamoya disease, [32] intracranial arterial stenoses, [33] and systemic vasculopathy among East Asian populations [32] and CAD in the Japanese population. [33] Recently, the signi cance of RNF213 and SLC26A11 in Caucasian populations were reported as well, [28] which encourages its reevaluation within other ethnicities. RPTOR is a component of the mTOR pathway, which regulates cell growth in response to nutrient levels by associating with the mammalian target of rapamycin (mTOR).…”
Section: Discussionmentioning
confidence: 99%